Media Pembelajaran Interaktif Pengenalan Batik Garutan Berbasis Android Menggunakan Augmented Reality - Sri Rahayu; Moch. Akmal Al Muyasar (Institut Teknologi Garut, 2026)
The decline in interest among the younger generation in local culture, especially Garutan Batik, is a problem that needs to be addressed immediately. Interactive and technology-based educational media are considered capable of addressing this challenge. This study aims to develop interactive learning media based on Augmented Reality (AR) to introduce Garutan Batik motifs to children and teenagers. The development was carried out using the Multimedia Development Life Cycle (MDLC) method, which includes the stages of concept, design, material collecting, assembly, testing, and distribution. The application was designed using Unity and Vuforia SDK, and presents three main features: batik pattern recognition, AR-based 3D visualization, and gamification-based interactive quizzes. Alpha testing results showed that all features worked well without any obstacles. Meanwhile, beta testing on 21 respondents showed a user satisfaction rate of 86.19%. This application is considered easy to use, interesting, and able to increase children's interest in Garutan Batik. The integration of 3D visualization, voice narration, child-friendly interface design, and a gamification approach makes this application an effective and enjoyable educational medium. Thus, the use of AR technology in learning media has been proven to increase understanding and preservation of local culture in an innovative way.